Kinetic H/D Exchange Study of Co(III) Coordination Compounds of Diazines Using NMR Spectroscopy - FOROUGHIFAR, N.; MOBINIKHALEDI, A.; FOROUGHIFAR, NEDA; HOSEINI, SHARIE (Asian Journal of Chemistry, 2010)
The Co(III) diazines complexes having composition [(NH3)5CoPhtz)]- (ClO4)3 (1) (Phtz = phthalazine), [(NH3)5CoPydz)](ClO4)3 (2) (Pydz = pyradazine), [(NH3)5Co(3-Me-Pydz)](ClO4)3 (3) (3-Me-Pydz = 3-methyl pyradazine) and [(NH3)5Co(3-MePhtz)](ClO4)3 (4) (3-MePhtz = 3-methyl phthalazine), [(NH3)5Co(ImH)](ClO4)3 (5) (ImH = imidazole), [(NH3)5Co(NMeIm)]( ClO4)3 (6) (N-MeIm = N-methylimidazole) undergo OD–-catalyzed H/D exchange at the ortho position of the coordinated site. Rate constants for H/D exchange of these complexes at 25°C or 60°C were obtained in alkaline D2O solution using NMR spectroscopy. Reaction rate for [(NH3)5CoPhtz)](ClO4)3, [(NH3)5CoPydz)](ClO4)3, [(NH3)5Co(3-Me- Pydz)](ClO4)3 and [(NH3)5Co(3-MePhtz)](ClO4)3 at 25°C are faster compared to [(NH3)5Co(ImH)](ClO4)3, [(NH3)5Co(N-MeIm)](ClO4)3 (7). However [(NH3)5CoImCo(NH3)5]Br5 complex does not H/D exchange at 60°C even in strong alkaline D2O solution.